Beyond hypertension - Gamboa Aboado, Raúl (2010)
In this paper, the authors want to review the following aspects: a) the techniques for measuring blood pressure, b) physiology of blood pressure, c) pathophysiology and natural history of high blood pressure disease, d) its importance as a cardiovascular risk factor and its association with other risk factors, e) therapy of high blood pressure, f) resistant and refractory high blood pressure, and g) hypertensive urgency and hypertensive crisis. This review emphasizes the importance of adequately reducing high blood pressure in hypertensive patients instead of routinely measuring blood pressure and offering appropriate therapy for just a few patients. As long as age increases in the whole population, the frequency of high blood pressure increases in every society, no matter whether it is an industrialized country or a developing country1; at the same time, in spite of the well-known dangers of uncontrolled high blood pressure, this condition is still inadequately treated all over the world2; partly because of carrying no symptoms during its first 15 to 20 years of occurrence. Inadequate management of high blood pressure is found both in strictly controlled communities, as well as within clinical trials assessing the use of antihypertensive drugs2,3. Consequently, cardiovascular risk remains high in most patients whether they receive therapy or not. All over the world, out of 7,6 million premature deaths, 13.5% of them are attributable to high blood pressure; this condition is responsible of 47% of all cases of coronary heart disease, and of 54% of all cerebrovascular accidents; half of this burden is observed between 45 and 69 years of age4. Blood pressure measurements are the simplest way for identifying persons at risk for premature death.